VARIASI MODEL SILOGISME UNTUK PENGAMBILAN KESIMPULAN DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Elly’s Mersina Mursidik (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2011)
Logical argumentations are required in communication and interactions between students and teachers. Classroom activities lead continuous or discontinuous communication and interactions. This is due to the questions by the teacher to the students contains logical truth. The value of the logical truth makes the teaching and learning activities run as they are planned. Questions for the students should be tautologies rather than those contradictory.